Foreign language aptitude theory: Yesterday, today and tomorrow. (21st December 2016) - Wen, Zhisheng (Edward); Biedroń, Adriana; Skehan, Peter
Abstract : Foreign language (FL) aptitude generally refers to a specific talent for learning a foreign or second language (L2). After experiencing a long period of marginalized interest, FL aptitude research in recent years has witnessed renewed enthusiasm across the disciplines of educational psychology, second language acquisition (SLA) and cognitive neuroscience. This paper sets out to offer a historical and an updated account of this recent progress in FL aptitude theory development and research. As its subtitle indicates, the paper centres on three major issues: following the introduction and clarification of basic concepts, Section 1 traces the early conceptions of FL aptitude dominated by John Carroll's pioneering work.Section 2 summarizes and examines more recent theoretical perspectives and FL aptitude models proposed by researchers from multiple disciplines that have significantly broadened the conventional research traditions associated with Carroll's original conception. Based on the research synthesis of current FL aptitude models, Section 3 suggests the directions FL aptitude theory and research might take in coming years. We conclude that a working memory perspective on FL aptitude presents one promising avenue for advance, as does the development of new aptitude tests to predict speed of automatization, implicit learning and greater control over an emerging language system. In addition, it is argued that issues of domain-specificity versus domain-generality for aptitude tests may lead to aptitude theory and research becoming more central in applied linguistics.